The effect of consuming nuts on cognitive function: a systematic review and meta-analysis of randomized clinical trials - Moabedi, Mahdi; Aliakbari, Mohammadreza; Erfanian, Shima; Jibril, Aliyu Tijani; Milajerdi, Alireza (Frontiers in Nutrition, 2024)
Background: Results from clinical trials investigating the effect of nuts consumption on cognition are conflicting. We decided to conduct the current meta-analysis to summarize all available evidence on the effect of consuming nuts on cognition scores.We conducted a comprehensive search in the online databases using relevant keywords up to June 2024. We included all the published Randomized clinical trials (RCTs) investigating the effect of nuts, compared to control, on cognition scores.Results: Overall, 5 trials were included with a total sample size of 928 adults. Based on 6 effect sizes from these 5 trials, we did not find a significant effect of nuts on cognition function [Standardized Mean Difference (SMD): 0.27, 95% CI: -0.65 to 1.19, P =0.57].Our review could not find a significant effect of nuts on cognition function. Future high-quality RCTs with larger sample sizes should be conducted to shed light on the impact of nuts on cognition.